2019
DOI: 10.14712/23362936.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Complications Following a Trans-masseteric Antero-parotid Approach for Patients with Sub-condylar Fractures of Their Temporomandibular Joint. A Retrospective Study

Abstract: Sub-condylar fractures of the temporomandibular joint can be treated by an extraoral or intraoral approach. Trans-masseteric antero-parotid approach (TMAP) is an extraoral approach utilising a retromandibular incision. The authors evaluated patients’ status and any complications of using TMAP from the years 2013–2017. There were 39 patients (44 fractures). When using TMAP, in 43 fractures the fragments were favourably positioned, in one case the position was compromised. Of the complications, postoperative pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Studies by Vesnaver et al .,[ 17 ] 2005; Bindra et al ., 2010;[ 18 ] Bhutia et al ., 2013;[ 10 ] Shi et al ., 2015;[ 9 ] Ghezta et al ., 2016;[ 11 ] Kanno et al ., 2016;[ 19 ] Bruneau et al .,[ 12 ] 2016 and Parihar et al ., 2019[ 20 ] showed both displacement and dislocation of condylar fractures. All other studies[ 5 16 21 22 23 ] showed only displacement of the condyle, whereas Imai et al ., 2019;[ 7 ] Imai et al ., 2020[ 26 ] showed isolated condyle dislocation [ Graph 4 and Table 2 ].…”
Section: Resultsmentioning
confidence: 98%
“…Studies by Vesnaver et al .,[ 17 ] 2005; Bindra et al ., 2010;[ 18 ] Bhutia et al ., 2013;[ 10 ] Shi et al ., 2015;[ 9 ] Ghezta et al ., 2016;[ 11 ] Kanno et al ., 2016;[ 19 ] Bruneau et al .,[ 12 ] 2016 and Parihar et al ., 2019[ 20 ] showed both displacement and dislocation of condylar fractures. All other studies[ 5 16 21 22 23 ] showed only displacement of the condyle, whereas Imai et al ., 2019;[ 7 ] Imai et al ., 2020[ 26 ] showed isolated condyle dislocation [ Graph 4 and Table 2 ].…”
Section: Resultsmentioning
confidence: 98%
“…6,7 The retromandibular anteroparotid approach based on the skin incision modification of Wilson transmasseteric anteroparotid approach was first described independently by Parihar et al and Machon et al in 2019. 3,8,9 The retromandibular transparotid approach (RTA) was first introduced by Ellis and Dean in 1993 and the subparotid variant in 2021 by Bruneau et al and Scolozzi and Foletti in the years 2018 and 2020, respectively [10][11][12] Retromandibular transparotid approach traverses the parotid gland and enables exposure of the entire ramus and condylar neck from behind the posterior border. The primary advantage is the most direct proximity of skin incision to the area of interest compared to other transfacial approaches, of course with the number of possible complications described.…”
mentioning
confidence: 99%
“…The retromandibular retroparotid approach was first reported by Chossegros et al in 1996, but the retroparotid access from the lazy “S“ incision has been already known since 1978 6,7 . The retromandibular anteroparotid approach based on the skin incision modification of Wilson transmasseteric anteroparotid approach was first described independently by Parihar et al and Machon et al in 2019 3,8,9 . The retromandibular transparotid approach (RTA) was first introduced by Ellis and Dean in 1993 and the subparotid variant in 2021 by Bruneau et al and Scolozzi and Foletti in the years 2018 and 2020, respectively 10–12 …”
mentioning
confidence: 99%